Navigating tiwala in disasters rural women leaders and social constructions of trust with international humanitarian organisations - Medina, Kara Danielle (Review of Women's Studies, 2024)
Access online through this link: https://journals.upd.edu.ph/index.php/rws/article/view/9962/8796